Resistências contraditórias do campesinato em Diamante do Sul/PR: uma abordagem da subordinação da renda da terra no sistema integrado da sericicultura - Arruda, Vanessa Bueno (2023)
This work proposes to problematize the peasantry's relationship with the integrated sericulture system, from the spatial perspective of peasants in the municipality of Diamante do Sul-PR, linked to the contract system by the capitalist industry. It seeks to understand the peasant resistance amid the subordination of land income, being a contradictory relationship, in which industrial capital monopolizes the peasant territory in favor of the accumulation of its wealth. Sericulture peasants live on small properties, seeking survival strategies beyond the production of silkworms, in order to maintain their family way of life and their permanence in the countryside. Thus, through the theoretical contribution, it is understood that the peasantry is not disappearing, but is inserted in the capitalist mode of production, which, contradictorily, is related to a diversity of crops, which is part of its family organization. In this sense, it deepens how the peasantry recreates itself from this monopolization of the territory by the capital of sericulture. That is, field analysis seeks to deepen the understanding of peasant recreation in the face of the monopolization of the territory by capital un sericulture.